The chemistry of contrast agents in medical magnetic resonance imaging - Helm, Lothar.; Merbach, André E.; Tóth, Éva. (John Wiley & Sons Inc., 2013)
"The second edition of The Chemistry of Contrast Agents in Medical Magnetic Resonance Imaging is a comprehensive treaty covering all aspects of production, use, operating mechanism and theory of these diagnostic agents used to produce high contrast images in MRI.It has been completed to now include recent developments on "classical" Gd-based and iron-oxide probes and chapters dedicated to the most significant advances in molecular imaging probes. Chemical Exchange Saturation Transfer is discussed, which is a novel means of generating MRI contrast"--